Antibiotic resistance of Helicobacter pylori in Nanjing, China: a cross-section study from 2018 to 2023 - Wei, Wenjuan; Wang, Zhibing; Li, Chao; Jiang, Zongdan; Zhang, Zhenyu; Wang, Shukui (Frontiers in Cellular and Infection Microbiology, 2023)
Background The increasing prevalence of antibiotic resistance in cases of Helicobacter pylori (H. pylori) infection has emerged as a significant global issue. This study offers a comprehensive examination of the alterations in drug resistance exhibited by H. pylori in the Nanjing region of China during the preceding five years. Another important objective is to investigate the influence of levofloxacin medication history on genotypic and phenotypic resistance. Methods This research screened 4277 individuals diagnosed with H. pylori infection between April 2018 and May 2023. The phenotype and genotypic resistance were evaluated using the Kirby-Bauer disk diffusion and PCR method. Results The most recent primary resistance rates for metronidazole, clarithromycin, levofloxacin, amoxicillin, furazolidone, and tetracycline were recorded at 77.23% (2385/3088), 37.24% (1150/3088), 27.72% (856/3088), 0.52% (16/3088), 0.19% (6/3088), and 0.06% (2/3088), respectively. For the recent five years, we observed a notable upsurge in the rate of metronidazole resistance and a slight elevation of clarithromycin and levofloxacin resistance. The documented resistance rates to single-drug, dual-drug, triple-drug, and quadruple-drug regimens were 35.39%, 28.32%, 25.72%, and 0.21%, respectively. The prevalence of multidrug-resistant strains escalated, rising from 37.96% in 2018 to 66.22% in 2023. The rate of phenotypic and genotypic resistance rate (57.10% and 65.57%) observed in strains obtained from patients without a levofloxacin treatment history was significantly lower than the rate in strains obtained from those with a history of levofloxacin treatment (88.73% and 94.74%). The prevailing gyrA mutations were primarily N87K (52.35%, 345/659), accompanied by D91N (13.96%, 92/659), and closely followed by D87G (10.77%, 71/659). For gyrA mutations, the 91-amino acid mutants exhibit a higher likelihood of discrepancies between phenotypic and genotypic resistance than the 87-amino acid mutants. Conclusion The extent of antibiotic resistance within H. pylori remains substantial within the Nanjing region. If levofloxacin proves ineffective in eradicating H. pylori during the initial treatment, its use in subsequent treatments is discouraged. The employment of levofloxacin resistance genotype testing can partially substitute conventional antibiotic sensitivity testing. Notably, predicting phenotypic resistance of levofloxacin through PCR requires more attention to the mutation type of gyrA to improve prediction accuracy.